2016
DOI: 10.3171/2016.3.spine151491
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vancomycin powder on human dural fibroblast culture and its implications for dural repair during spine surgery

Abstract: OBJECTIVE Surgical site infections (SSIs) are a major source of morbidity after spinal surgery. Several recent studies have described the finding that applying vancomycin powder to the surgical bed may reduce the incidence of SSI. However, applying vancomycin in high concentrations has been shown in vitro to inhibit osteoblast proliferation and to induce cell death. Vancomycin may have a deleterious effect on dural healing after repair of an intentional or unintentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 21 publications
0
28
0
4
Order By: Relevance
“…Moreover, a positive correlation between this effect and the icariin concentration was observed. However, in previous studies, cell numbers were reduced by 50% compared with the control group at 24 h after they were co-cultured with 0.4 mg/mL vancomycin and human dural fibroblast ( Goldschmidt et al, 2016 ). The differences might be due to the variety of species and genera of the cells, and the different characteristics of cellular metabolic activity.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, a positive correlation between this effect and the icariin concentration was observed. However, in previous studies, cell numbers were reduced by 50% compared with the control group at 24 h after they were co-cultured with 0.4 mg/mL vancomycin and human dural fibroblast ( Goldschmidt et al, 2016 ). The differences might be due to the variety of species and genera of the cells, and the different characteristics of cellular metabolic activity.…”
Section: Discussionmentioning
confidence: 89%
“…In fact, a high dose of VCS (more than 1 g of vancomycin) was usually implanted into the local site to control the repeated infection in some cases. In addition, a previous study indicated that a high concentration of vancomycin (more than 4 mg/mL) can decrease the number of osteogenic cells, induce a loss in pseudopodia formation and alter the normal shape of the cytoplasm ( Rathbone et al, 2011 ; Goldschmidt et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ein signifikanter Zelltod wurde bei einer Dosierung über 6 mg/cm 2 beobachtet [57]. Gleichzeitig konnte ein dosisabhängiger negativer Einfluss auf humane durale Zellkuturen beobachtet werden [58]. In vivo konnte in einem Rattenmodell keine höhere Pseudarthroserate bei der Verwendung von Vancomycin als Puderapplikation im Wundbereich mit einer 10fach höheren Dosis als das Gewichtsäquivalent (143 mg/kg Körpergewicht) nachgewiesen werden [59].…”
Section: Lokale Antibiotikaanwendungen Im Rahmen Operativer Versorgungenunclassified
“…Many articles, including systematic reviews, meta-analyses, and clinical trials, have confirmed that using intrawound vancomycin powder during spine surgery could provide considerable benefits with few side effects [ 1 2 3 4 5 6 7 8 ]. However, some in vitro , animal, and human studies suggest that vancomycin powder inhibits the osteoblast and dural cell viability [ 9 10 11 ]. Furthermore, some studies have shown that using vancomycin intraoperatively has potential risks, including dose-dependent inhibiting effects and changes in microbial trends [ 10 12 13 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some in vitro , animal, and human studies suggest that vancomycin powder inhibits the osteoblast and dural cell viability [ 9 10 11 ]. Furthermore, some studies have shown that using vancomycin intraoperatively has potential risks, including dose-dependent inhibiting effects and changes in microbial trends [ 10 12 13 14 ]. One retrospective study revealed that the intraoperative microbial trends in surgical site infections appeared to be different in patients in whom intrawound vancomycin powder was used during spine surgery than those in patients who did not; however, the investigators did not examine the relationship between the vancomycin dose used and types of infection bacteria [ 12 ].…”
Section: Introductionmentioning
confidence: 99%